Influence of additives on combustion of ultradisperse aluminum powder and chemical binding of air nitrogen; Combustion, Explosion, and Shock Waves; Vol. 32, iss. 2 - Ilyin A. P. Aleksandr Petrovich (1996, 1996)
Experimental results are presented on combustion in air of ultradisperse aluminum powder with additives of ultradisperse powders of copper, nickel, iron, tin, silicon, graphite, boron, tungsten, and molybdenum.X-Ray diffraction and chemical analyses were used to study the composition of the end products. A tin additive has an inhibiting action on the chemical combining of air nitrogen as aluminum nitride and oxynitride, whereas iron, tungsten, and molybdenum additives favor an increase in nitrogen content. As is established, the influence of additives on the processes determining the duration of two combustion stages is greater than on the content of bound nitrogen in the products.